Gilles Deleuze : key concepts - Stivale, Charles J. (Key concepts., 2014)
Gilles Deleuze is now regarded as one of the most radical philosophers of the twentieth century. His work is hugely influential across a range of subjects, from philosophy to literature, to art, architecture and cultural studies. ""Gilles Deleuze: Key Concepts"" provides a guide to Deleuzian thought for any reader coming to his writings for the first time. This new edition is fully revised and updated and includes three new chapters on the event, psychoanalysis and philosophy.